Indeks Antropometri sebagai Alat Skrining Diabetes Melitus Tipe 2: Anthropometries Indexes as A Screening Tool for Diabetes Mellitus Type 2 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The incidence of diabetes mellitus (DM) tends to increase and it is believed that over 50% are undiagnosed. Mass screening using blood glucose test can be done to find out the undiagnosed DM but not recommended due to high cost. Therefore, a cheap, easy, and accurate alternative method is needed. Ninety percents of DM type 2 are obese. The present study was designed to examine the anthropometric indexes as a screening tool for DM type 2. This study performed was a cross-sectionally and a diagnostic test of anthropometries indexes, using BMI (Body Mass Index), WC (waist circumference), WHR (waist to hip ratio), and WtHR (waist to height ratio) for DM type 2 screening. Subjects were 1.382 male and female age 30-55, living at 5 sub villages in Johar Baru village, Central Jakarta without any chronic and severe diseases. The gold standard for DM diagnosis, capillary blood sugar level were tested with Advantage II Monitor. There were 9,6% people with DM found and 6,1% were undiagnosed DM. The sensitivity and specificity were not both more than 80% for any cut off points either alone or combined. The balance score for both was about 60%. The hypothesis testing for a single population proportion at a=0,05 (1 sided) could not conclude that both sensitivity and specificity were more than 80% at each cut off point selected. In conclusion, the best anthropometries indexes used as DM screening tool for the whole subjects was WtHR at cut off point 0,522 with 82,2% sensitivity and 52,7% specificity